Impact of Incentive Spirometry in COPD Exacerbations: A Comparative Study - Paudel, Bishal; Panthi, Bishal; Shrestha, Rakshya; Karki, Onika; Dhungana, Reechashree; Yadav, Alisha; GC, Saroj; Neopane, Arpana (Journal of Institute of Medicine Nepal, 2024)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a major cause of morbidity and mortality in Nepal, with acute exacerbations (AECOPD) leading to severe complications. This study explores the impact of incentive spirometry (IS) on clinical outcomes, arterial blood gases and hospital stay in AECOPD patients.Methodology: This comparative study was conducted at a tertiary care center in Kathmandu, Nepal and involved 60 AECOPD patients, split into two groups: 30 receiving standard medical treatment (control) without IS and 30 using IS. Demographic and clinical information were recorded and key outcomes— arterial blood gases (ABGs), MMRC score, respiratory rate, oxygen saturation, and hospital stay—were measured after stabilization and at discharge. Statistical analysis used SPSS 22, with significance set at p